2023
DOI: 10.1186/s12967-023-04725-z
|View full text |Cite
|
Sign up to set email alerts
|

The epitranscriptome of high-grade gliomas: a promising therapeutic target with implications from the tumor microenvironment to endogenous retroviruses

Christian K. Ramsoomair,
Michele Ceccarelli,
John D. Heiss
et al.

Abstract: Glioblastoma (GBM) comprises 45.6% of all primary malignant brain cancers and is one of the most common and aggressive intracranial tumors in adults. Intratumoral heterogeneity with a wide range of proteomic, genetic, and epigenetic dysregulation contributes to treatment resistance and poor prognosis, thus demanding novel therapeutic approaches. To date, numerous clinical trials have been developed to target the proteome and epigenome of high-grade gliomas with promising results. However, studying RNA modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Anti-HIV retroviral drugs have demonstrated some benefit in ALS and they decrease HERV-K load after 24 weeks of therapy [194]. A strategy to augment tumor antigenicity via HERV-induced inflammation is another approach to fight cancer [149] including gliomas [195]. Moreover, it has been suggested that various tumors will be responsive to vaccines against HERV-K Gag [196].…”
Section: Treating Map/hervmentioning
confidence: 99%
“…Anti-HIV retroviral drugs have demonstrated some benefit in ALS and they decrease HERV-K load after 24 weeks of therapy [194]. A strategy to augment tumor antigenicity via HERV-induced inflammation is another approach to fight cancer [149] including gliomas [195]. Moreover, it has been suggested that various tumors will be responsive to vaccines against HERV-K Gag [196].…”
Section: Treating Map/hervmentioning
confidence: 99%
“…A strategy to augment tumor antigenicity via HERV-induced inflammation is another approach to fight cancer [149] including gliomas [195]. Moreover, it has been suggested that various tumors will be responsive to vaccines against HERV-K Gag [196]. Thus, HERV-targeting agents could provide a broad new class of therapeutics for autoimmunity, neurodegeneration and cancer.…”
Section: Treating Map/hervmentioning
confidence: 99%